The Role of Adipose-Derived Stem Cells in Breast Cancer Progression and Metastasis - Riccardo Schweizer; Wakako Tsuji; Vijay S. Gorantla; Kacey G. Marra; J. Peter Rubin; Jan A. Plock (Stem Cells International)
Conventional breast cancer extirpation involves resection of parts of or the whole gland, resulting in asymmetry and disfiguration. Given the unsatisfactory aesthetic outcomes, patients often desire postmastectomy reconstructive procedures. Autologous fat grafting has been proposed for reconstructive purposes for decades to restore form and anatomy after mastectomy. Fat has the inherent advantage of being autologous tissue and the most natural-appearing filler, but given its inconsistent engraftment and retention rates, it lacks reliability. Implementation of autologous fat grafts with cellular adjuncts, such as multipotent adipose-derived stem cells (ADSCs), has shown promising results. However, it is pertinent and critical to question whether these cells could promote any residual tumor cells to proliferate, differentiate, or metastasize or even induce de novo carcinogenesis. Thus far, preclinical and clinical study findings are discordant. A trend towards potential promotion of both breast cancer growth and invasion by ADSCs found in basic science studies was indeed not confirmed in clinical trials. Whether experimental findings eventually correlate with or will be predictive of clinical outcomes remains unclear. Herein, we aimed to concisely review current experimental findings on the interaction of mesenchymal stem cells and breast cancer, mainly focusing on ADSCs as a promising tool for regenerative medicine, and discuss the implications in clinical translation.